KESEPAKATAN PERDAMAIAN OLEH MEDIATOR DI LUAR PENGADILAN - Pandu Nugroho; Wasiul Maghfiroh (Universitas Karya Husada Semarang, 2024)
The formation of a Peace Agreement between the parties shows that the mediation process was successful in resolving the conflict outside of court, but its position is not the same as a Peace Deed produced through mediation and implemented in court. To find out the legal basis for the difference in legal position between a Peace Agreement and a Peace Deed, thus this essay will undertake a legal study and analysis to determine how to guarantee that the two peace products have equal legal standing—that is, a position of evaluation of permanent legal norms. This study was conducted utilizing descriptive analysis techniques with a normative legal approach, based on statutory regulations. The study's findings demonstrate that the Peace Agreement's legal standing is on par with those of comparable peace accords. The opposite party may file a lawsuit in order to obtain legal recompense if the other party breaches the agreement. In the meantime, the Deed of Peace is fully enforceable, meaning that whichever party loses just needs to ask the court for execution. There are legal actions to improve the legal status of the Peace Agreement to a Peace Deed through litigation, based on legal provisions in Law No. 30 of 1999 and Perma No. 1 of 2016, although in reality raising the legal status can be accomplished utilizing a hybrid Arb-Med